Advances in the Epigenetic Mechanisms of Diabetic Nephropathy Pathogenesis - Zhang C; Xue S; Ren P; Han S; Zhou Y; Si Y; Han X; Zhang X; Zhang Y; Chen N; He H; Feng R; et al. (Diabetes, Metabolic Syndrome and Obesity)
Changlong Zhang,1 Song Xue,2 Peijun Ren,1 Shuaijie Han,2 Yu Zhou,2 Yingkui Si,2 Xue Han,2 Xiaoqian Zhang,2 Yanan Zhang,2 Na Chen,2 Hua He,2 Ran Feng,2 Lili Shang1,2 1Department of Acupuncture and Massage, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, People’s Republic of China; 2Department of Nephrology, Beijing Hospital of Integrated Traditional Chinese and Western Medicine, Beijing, People’s Republic of ChinaCorrespondence: Lili Shang, Email 15611426777@163.comAbstract: Diabetic nephropathy (DN) is one of the most severe microvascular complications of diabetes and a leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD). While traditional research has linked the onset of DN to factors such as metabolic dysregulation, inflammation, and oxidative stress, these mechanisms alone fail to fully explain the complex pathological features and individual variability of DN. In recent years, epigenetic research has provided new insights, revealing the critical roles of DNA methylation, histone modifications, and non-coding RNAs in the development of DN. DNA methylation regulates gene expression by altering methylation levels in promoter regions, affecting genes involved in inflammation and fibrosis. Histone modifications, including acetylation and methylation, influence gene transcription by altering chromatin structure. Additionally, non-coding RNAs, such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), play essential roles in gene expression networks. This review summarizes the latest advances in understanding these epigenetic mechanisms in DN pathogenesis, explores their roles in regulating inflammation, fibrosis, and cell damage, and discusses their potential applications in the diagnosis and treatment of DN. Further investigation into epigenetic modifications holds promise for identifying novel diagnostic markers and personalized therapeutic strategies for DN.Keywords: diabetic nephropathy, epigenetics, DNA methylation, histone modifications, non-coding RNAs